Arkæologiske undersøgelser på Oman halvøen - Frifelt, Karen (Kuml, 1968)
Archaeological investigations in the Oman peninsula A preliminary report The plain extended, savannah-like with its scattered trees, out toward the mountains. The sand blew before the wind, and settled in miniature dunes against the small thorn bushes around the camp where the Danish Archaeological Expedition had pitched its tents at the northern edge of the Buraimi oasis in the sheikhdom of Abu Dhabi, in the Oman peninsula of Arabia. While a team of six men were working at the same time in Saudi Arabia, it was a modest force which started work in Buraimi in the middle of January 1968: Eivind Lorenzen, an architect, and I, while Henning Nielsen joined us at the beginning of February. Work continued until the middle of April. As in previous years our expenses were covered by generous grants from the oil companies in Abu Dhabi: the Abu Dhabi Petroleum Company and Abu Dhabi Marine Areas. The latter in addition took care of all the large and small problems of the Expedition, from despatching our packing cases to acquiring the material for the cook's palm-leaf kitchen, while its representative in Abu Dhabi, Donald Deane, earned the gratitude of the Expedition for ever-present help and hospitality. Mounds large and small raised their rounded tops against the horizon. On several of the lower ones were found the ruined traces of houses, while several of the larger had certainly borne watch-towers such as those whose ruins could still be seen ringing the nearby village of Hili. Between them lay an ancient Islamic cemetery, with several graves still marked by a stone at the head and another at the foot. Low ridges on the level ground showed the run of long walls, which had once undoubtedly fenced in farms or gardens. Everywhere lay potsherds, in no great numbers, but sufficient to allow the greater part to be identified as Islamic, many of the same types as we knew from Bahrain, stretching back to the 13th and 14th centuries, with a few fragments of Ming ware and celadon among them. When we had rubbed the first dust-storm out of our eyes, and installed the Indian cook, P. C. Ummar, with his pans and spices, and the Pakistani chauffeur, Muhammad Akram, with the Expedition's hired land-rover and his own harmonica the work could begin. The first major project was the low tell, almost a kilometre long, which extended from north to south between the villages of Hili and Qatara, and which His Highness Sheikh Zayyid had earlier brought to the attention of the Expedition. Potsherds lay thick upon its top and sides, interspersed with fragments of small steatite vessels with incised ornamentation, while the outlines of clay-walled houses could also be made out on the surface. While the tell was being surveyed in, a section trench was laid out across it 2-300 metres from the southern end at a point where the clay walls were particularly sharply defined on the surface; in the first instance we set off an east-west trench, 2 metres wide, from the approximate centre of the ridge for 35 metres out towards the eastern edge, where a track ran along the edge of a growth of trees. A couple of hundred metres further to the east ran the course of the broad new road which was planned to run to Hili, and we took its clean-scraped "bed", according to the map 290 metres above sea-level, as the datum point for our levels. South of the tell work was in full progress on another motor road, and immediately beyond the road-works lay Qatara. To the north a few dunes and two mounds, of which one still bore the ruins of a tower, intervened between the tell and Hili, while to the west the yellow-red waves of the sand-dunes rolled close in upon the ancient settlement: the desert on the march across the oasis, though still sparing a few groups of trees. No wonder that Buraimi guards its trees, so that it is forbidden to break off boughs for fodder or fuel. "For if you do," warned Ummar, "the constable from Qatara will come." In the hollows between the dunes near the tell there often lay potsherds, either Islamic or unglazed sherds of the same type as those on the tell. It was soon obvious that the tell would to some degree disappoint our expectations, in addition to causing us a deal of trouble. It was not very high, 3-4 metres above the surrounding country, but since the surface layer was pre-Islamic we had hoped that it would give us a sizable section through Buraimi's prehistory, once we had removed the upper layer of drift-sand. Unfortunately it appeared that the drift-sand continued all the way both across and down. Only the upper three-quarter metre or so contained ash-pits, potsherds, and remains of clay walls and floors. The sides of the trench soon showed a tendency to slide inward; in the slightest wind we worked in a cloud of dust, and after several days' rain the sides collapsed even more. Both our workers and we were getting tired of "such quantities of sand". About 2 metres down, in sterile sand, we stopped work, and after two small test pits elsewhere on the tell gave the same result - a thin occupation level overlying sand -we finished off with an area-excavation of the "pillared house". Two metres south of the western end of the section trench, on the summit ridge of the tell, 6 clay plinths, apparently for roof-bearing pillars, stuck out from the sand, while the surrounding walls could be made out less clearly. When the area was cleared it could be seen that these walls had, under the action of wind and rain and sun, collapsed to form an irregular cap of clay over the top of the mound and a good way down each side. Only small stretches of wall, or rather of foundations, could be distinguished. They appeared to have been built of rectangular sun-dried bricks. The plinths had a square core, with sides measuring a half to three-quarters of a metre, which had then been added to with clay daub to give them a circular form. They stood in two parallel rows about three metres apart; the two westermost pairs were the same distance apart, while there was only a metre and a half to the easternmost pair. The size of the house could not be determined with certainty, but it had measured at least 9 X 6 metres. There were a number of ash-pits within the walls, probably secondary, and a hearth of clay and stones in association with fragments of worn clay flooring. Immediately above the floor and close to the hearth a lump of clay was found with an unclear, almost destroyed seal-impression, a clay bulla. At the same level, at the bottom of an ash-pit two metres from the hearth was found a leaf-shaped bronze arrowhead with a broad centre-rib, sloping shoulders and tang (as in Fig. 2 a). The northwest corner of the house, in which these finds were made, was the best preserved area. The only other objects recovered were small indeterminate scraps of bronze and potsherds. During the excavation and survey of the tell the whole surface was carefully searched, resulting in several interesting finds in addition to the potsherd material: a number of bronze arrowheads, the majority of the same shape as that found in the house, but also two with a more massive midrib and very narrow edges (as in Fig. 2 b); and two stampseals of steatite, one of them broken away at the middle; a little pendant amulet with a script-like incised ornamentation, also of steatite (Fig. 3), and finally fragments of small animal figurines of terracotta. Bowls of red ware with a conspicuous shoulder and a narrow flat or curved rim trending slightly inward or outward and a flat base (Fig. 4 a) are very common, as are bowls with a red or black wash, also with shoulder, curved rim and flat base. Both these vessels and the numerous steatite fragments with incised stroke ornamentation correspond to the Dibba culture on the east coast of the Oman peninsula [1]. The majority of the steatite vessels are small, with a flat or ring base, slightly inturned rim, and sometimes an open rim-spout. Herringbone ornamentation below the rim is very common, while a few fragments bear concentric circles. Flat lids occur. Many coarse potsherds, blackened and of gravel-tempered clay, doubtless belong to kitchen ware. A not infrequent minority of sherds are of fawn or red ware with lines of black or reddish-brown paint. Cross-hatching or rows of zigzags on the outside of the vessels below the rim is characteristic, while spirals occur on very fine red ware. On comparing the pottery and animal figurines with the material from Bahrain one would be inclined to date the site to the middle of the First Millennium B. C., or perhaps a little later. But the complete absence of glazed ware is noteworthy, while the two seals are difficult to ascribe to this date. One portrays a gazelle, a not unknown motif in Buraimi, apparently standing upon an altar; its style is more at home in the Second or Third Millennium than in the First. The broken seal shows a wasp-waisted individual holding in his extended right hand a long-shafted axe with a curved edge in front of his face. Parallels to the leaf-shaped arrowheads with a broad midrib, which form the most common type, are known from Tepe Guran in Persia [2], where they have been found in a grave dated by C14 to the 13th century B. C. Pottery comparison is difficult, so long as the Buraimi material consists of so comparatively few and small fragments, but the Guran pottery too bears painted geometric ornamentation, including cross-hatching. It seems thus likely that, despite the apparently thin occupation layer, there may be evidence for several occupations at intervals of centuries. This can only be determined by a more thorough study of the material and perhaps of the tell. One thing at least was certain. The pottery did not in any way resemble that found in the round tomb structure some two kilometres east of Hili, which was excavated during the two previous seasons in Buraimi [3], nor that found in the settlement on Umm an-Nar. This tomb structure near Hili, with its 12 metre diameter and its immense stone slabs, originally standing in at least two courses, had been an impressive monument. The excavators had found on one of the smaller slabs a picture of an oryx in shallow relief. Unfortunately the majority of the larger slabs lay with the smooth outer surface, on which further reliefs might occur, downwards, and there had been no means at hand to lift the colossally heavy and unwieldy blocks. But now, three years later, enough of the soil supporting one of the stones had crumbled away so that three new animal figures had appeared. With the help of the Trucial Oman Scouts from Fort Jahili, who brought with them two trucks with winches, we succeeded in raising the stone on edge, and two remarkable, long-legged animals with long curved tails, holding a gazelle between them, could be photographed (Fig. 5 b). Although the animals in fact most resemble monkeys they were undoubtedly intended by the artist to represent lions. Two opposing lions with an animal between them form a motif not uncommon on Mesopotamian seals. The reliefs stand clear and sharp on the greyish-brown, somewhat layered sandstone. The block is the lower portion of the northern door-stone, which has been broken across at the porthole entrance. The upper, and larger, portion of the slab, with its stepped top, lay so firmly on its face that it was initially impossible to move it. We accordingly turned our attention to the south door-stone, whose upper half had broken into two and was correspondingly easier to wrestle with. We could moreover feel by hand slight irregularities on the down-turned side and even, in the oblique light of the afternoons, make out figures which resembled human forms. Excitement was high when the Trucial Oman Scouts, once more summoned, drove their trucks into position and brought their winches and chains into play. The operation was carried out successfully, without further damage to the reliefs. They turned out to represent two human figures hand in hand between and below two oryx with their long, slightly curved horns pointing backward (Fig. 1). They are very schematically represented, and the human figures have no features, but the free arm of one of them ends in a large hand with the individual fingers represented. Whether the same is true of the other figure cannot be determined because of the break in the stone. The lower half of the south door-stone lay leaning against the foundation blocks, so that it was possible to see its lower face. The surface was very damaged, and there appeared to be nothing left of the reliefs which it probably originally bore. As it could only be turned at the risk of damaging the upper relief it was left for the moment in peace. Instead, the upper part of the north door-stone was finally winched up on edge and carefully lowered with its ornamented side uppermost (Fig. 5). There were two reliefgroups on this stone: a scene of sexual intercourse (Fig. 5 c) and a group which we entitled (with complete disregard for chronology) the "Flight into Egypt" (Fig. 5 d). In front went a quadruped, by all the evidence a donkey, with a human figure riding sidesaddle, with one hand on the neck of the animal and the other holding the tail in a firm grip. The sex of the figure is not indicated, but the hair or headdress forms a halo around the head. Behind the animal follows another human figure, carrying in half-extended hands what appear to be two sticks, perhaps a sword and a bow. While we had previously discovered, on the stones of the tomb structures of Umm an-Nar, representations of single animals, a camel, a bull, a snake, here we met a more communicative art, which brings us closer to the people of the period. But which period? The style of the reliefs does not date them, but we may assume that they are an integral part of the tomb, the pottery of which is connected with that of the Kulli culture in Baluchistan, thus dating the pictorial slabs to the Third Millennium. At a time when we in Denmark were building dolmens and passage graves, while Egypt was raising its pyramids, the Oman peninsula, too, had its megalithic graves. Behind so imposing a grave-monument as the round structure in Buraimi one would expect to find an organized and prosperous community. Where had it carried on its day-by-day life? Close to the monumental tomb at the foot of the mountain chain of Jebel Auha lay a number of low mounds with potsherds and stone chippings on their tops, some with a single stone slab or so sticking up above the surface, most of them undoubtedly the remains of comparable tomb structures. Even 3-4 kms. to the north, almost buried in the sand dunes which stream in across the plain from the west, the undoubted ruins of a plundered tomb were found. At a few points quite small ridges, scarcely visible above ground surface, ran out from the mountains over the plain, old subterranean aqueducts, aflaj (sing. falaj). Here and there a well connected to the aflaj broke the surface, and in its stone-set sides we could sometimes recognize the small square foundation stones from the tombs. But no tell caught the eye. A ridge between the tomb area and Hili tempted us to a few days' excavation, as the sherds on its surface corresponded to those on the tell south of Hili, and as we had found close up to it a very fine and complete shouldered bowl with rim-spout standing bottom-uppermost with its base just visible in the sand (Fig. 4 b). But again there was only a thin surface layer, below which we reached, for a change, not sand but sterile gravel. We had gradually become so familiarized with the tomb area that we felt capable of distinguishing "round structures" from "other mounds". Immediately north of the tomb with the reliefts lay an irregular row of these "other mounds" terminating at the more distant end in a larger and finely rounded mound. After innumerable turnings up of spadefuls of soil had covinced us that they were not sand-dunes, but contained both potsherds and settlement earth, we selected a large flattish mound, about 40 metres in diameter, close to the excavated tomb structure. From the centre of the mound we laid out a trench, 2 metres wide, for 20 metres toward the west, to where we estimated the edge of the mound to be. Our workers' delight at having moved out to the "big stones" lasted a few days, until they discovered that in all its length the trench, under a layer of surface sand only a few cms. thick, consisted of hard clay. We too had our doubts, and laid out a corresponding trench toward the north. The result was the same. We laid out a larger area in the southwestern quadrant of the mound, extending further to the west than the end of the west trench. Right out here, on the level plain, we uncovered close below the surface a belt of large unshaped stones, with so much order in their ranks as to give the impression of being the foundations of a wall. For the moment it could not be determined whether the wall pursued a straight course or circled around the mound. Up the sides of the mound itself stretched the solid cap of clay. And while the southern wind blew the heat and dust of the Rub' al-Khali desert in over us, smarting our skin, splitting our lips and roughening our throats with thirst, we brushed and scraped the large clay surface, until walls of large rectangular dried-clay bricks began to come reluctantly into view. While the north-south trench lay deserted, we went hard to work on the other, and close to its western end we were able to dig down between two north-south-going walls, each over a metre thick. At a depth of between 3 and 4 metres we had passed through several clay layers resembling floors, and where we reached the foundation of one wall another wall would start and continue downward, but not immediately below the higher wall, so that the space available gradually narrowed to unpleasantly small proportions. Work in the trench was not popular. It was refreshing to come up to the surface, and take a mouthful of cool water from the goatskin in the shade of a tree, looking out over the oasis where flocks of sheep and black goats skipped lightly over stones and hillocks, and drove in over our mound with no respect for our marking posts and twine, while close in under the mountains a string of camels or a truck in its cloud of dust followed the old caravan trail to Dubai. There were no "small finds" apart from potsherds, but this was scarcely odd because only in the trench did we reach any real floor level. The area excavation yielded fair quantities of sherds, mostly of fairly coarse character, many recalling strongly the pottery of the Umm an-Nar settlement. The trench gave only few sherds, but from the deeper levels these included some painted fragments - black linear designs on fine red ware - which corresponded to the burial pottery from the round tomb. In the larger area we met with several fire-pits and one clay-built hearth, while in the trench we cut through two pits, dug down from near the surface and filled with ashes and charcoal. We are grateful to Mobil Oil, who very kindly arranged for two samples from one of these pits, taken about 50 cms. below the surface, to be Carbon 14-tested for us at their laboratory in New York; no more than two months after our return home we knew, therefore, that it was not bedouin camp-fires from recent centuries that we had so carefully cut through. The results read 3196 ± 156 and 3403 ± 161 Before Present [4], a not unduly large discrepancy, which enables us to date the upper disturbances of the mound, which so far as we could see have no connection with the massive mud-brick walls, to about the 14th century B. C. To reach the bottom of the occupation layers, to extricate the walls, and to determine whether the adjoining mounds really cover a settlement of a size and quality to match its burial monuments, must be the objects of coming seasons' work. Most of our investigations had lain north of the centre of Buraimi, AI-Ain, but doctors and nurses from the American hospital south of that town had picked up potsherds and steatite fragments related to those of the round tomb in the area east of the cliffs near their hospital; we accordingly reconnoitred a considerable area here. Potsherds lay very thick, but they were practically all of Islamic origin. It is possible that the few earlier objects have been washed out of vanished mounds. The season drew to a close. The cold nights had become milk-warm; the plain, which after the rain had blossomed and grown green, became a gray dusty expanse, where the scarab-beetles rolled their balls of camel-dung. Round about us the modern Buraimi grew up vigorously. The school-bus every day drove the children in to Al-Ain, where buildings of cement were replacing palm-huts and clay houses. Excavators and bulldozers roared by day and by night, and immense roadworks stretched their ribbons between the villages, while roundabouts shot up like toadstools in the course of a single night. Experimental farms and afforestation attempt to check the movement of the sand, and research on aquifers and water reserves will ensure that the vital water, which created Buraimi, does not suddenly fail. On the route, almost 200 kms. long, to the capital city of Abu Dhabi on the coast, roads and water-lines are being built, a gigantic undertaking. Most impressive, perhaps, is the way in which the bedouin jump straight from the Middle Ages into the twentieth century. An old bedawi will mount into the aircraft, lay his camel-stick aside and fasten his seat-belt with the same nonchalance as he later will mount his camel or his truck. His Highness Sheikh Zayyid personally negotiates and leads the million-pound projects which he has initiated in his desert kingdom, but he still takes the time to travel in the traditional fashion from village to village in the oasis and to hold the majlis (assembly) where anyone may come to him and present his views and problems, while the Sheikh listens and smokes his tiny bedouin pipe. May the camel-stick, and the undisturbed dignity which characterizes its little community, accompany Abu Dhabi on its way into the oil-period. After the termination of our work in Buraimi a reconnaissance was carried out in Sharjah, where the ruler, His Highness Sheikh Khalid bin Muhammad al-Qasimi, had sent us a message, that archaeological discoveries had been made in his sheikhdom, with an invitation to come and see the discoveries. In the course of investigations of water resources which have been carried out during the latest years the Trucial States Water Resources Survey had encountered inland near Tawi Mulayha ruins of buildings and potsherds. His Highness had personally in the course of hunting made two valuable discoveries in the sand: a pair of crescent-shaped gold earrings and a little alabaster vessel with two compartments and lug-handles formed as schematic animal heads, together with a little flat-based bowl (or lid?) of the same material. The earrings may be Islamic, but the two objects of alabaster resemble objects from Bahrain, of Hellenistic date. In the course of a reconnaissance with the Trucial States Water Survey it was confirmed that an old Islamic cemetery exists on the site, together with quantities of Islamic sherds, many of which seem to be of early Islamic date. But on low mounds in the neighbourhood there were also glazed pre-Islamic sherds which could agree very well in date with the alabaster vessels. In addition to His Highness, two archaeological enthusiasts, Sheikh Khalid bin Sultan and John Nisbet from International Aeradio, possessed large collections of potsherds which confirmed this conclusion. Further to the south, in the area of Madan, lay groups of tumuli of a size and shape reminiscent of Danish Bronze-Age mounds. Towards the east in Wadi Hatta, which runs up into the mountains, on the border of Muscat, rock carvings were found on large free-lying blocks of stone. A munificent spring of water here broke forth, and had transformed the site, in the otherwise parched mountain pass, into a garden of green plants and flowering oleanders. The carvings, often of mounted men, cannot in themselves be dated, but the site undoubtedly lies on one of the old caravan roads across the Oman peninsula. That these regions were the scenes of lively activity in both trade and war during Islamic times is well-attested. And the ancient aqueducts bear witness of a considerably larger population in former times than now. A little north of Tawi Fili such a falaj had been cut through, exposing the irregular limestone slabs of which it had been built. A couple of fairly complete pottery vessels discovered in it are Islamic, probably of the 13th-14th century. But it is certain that both Sharjah and Dubai have a history longer and more eventful than they yet have dreamed. Karen Frifelt